Landscape Targeted Crop-Fertilizer Response in the Highlands of Ethiopia Version 1.0 - International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2021)
The dataset is meant for developing fertilizer management decision support tool for an effective crop-nutrient management. The dataset is developed on the basis of landscape targeting on-farm trials on crop-nutrient response and crop yield gap assessment across the Africa Rising target districts and other scaling up locations in the Ethiopian highlands.